Stability Indicating Spectrophotometric and Chemometric Methods for Determination of Aripiprazole in Presence of its Degradation Products, A Comparative Study. Issue 2 (4th March 2019) - El-Maraghy, Christine M.; Salem, Hesham; Amer, Sawsan M.; Nebsen, Marianne
Abstract: Simple, accurate, selective and validated stability indicating UV spectrophotometric univariate and multivariate methods were developed for determination of Aripiprazole in presence of its alkaline and oxidative degradation products. The developed univariate methods; derivative ratio spectra-zero crossing, successive derivatives of ratio spectra and mean centering of ratio spectra. The first one used the amplitude of the first derivative ratio signals at 303.0 nm, the second method depended on the successive derivative of ratio spectra in two steps and measuring the absorbance of Aripiprazole at 281.0 nm and the third one measured the mean centered values oat 294.0 nm. Two chemometric multivariate methods were applied; principal component regression (PCR) and partial least-squares regression (PLS). The selectivity of the proposed methods was confirmed using laboratory-prepared mixtures. The obtained results were statistically compared with those obtained with the manufacturer HPLC method, showing no significant difference with in accuracy and precision. These methods could be applied as stability indicating methods for the determination of Aripiprazole in presence of its degradation products, in bulk powder or in pharmaceutical formulations.